2020
DOI: 10.1186/s12917-020-2242-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphine plasmatic concentration in a pregnant mare and its foal after long term epidural administration

Abstract: Background Epidural administration of morphine has been shown to be an effective analgesic strategy in horses; however, the possible occurrence of side effects limits its usage. In order to decrease their frequency, it is important to target the minimal effective plasma concentration and avoid overdosing. As to date species-specific pharmacokinetics data are not available for epidural morphine, the dosing regimen is usually established on the basis of clinical reports and personal experience. In certain physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Thus, sedation is a relatively common CNS side-effect of epidurally administered alpha-2 agonists, opioids and dissociative drugs (Table 1). In contrast, CNS excitation is a rare side-effect and has only infrequently been reported in horses after the epidural administration of large doses tiletamine/zolazepam (Natalini et al 2004a) and the opioids morphine and tramadol (Giorgi et al 2010;Mirra et al 2020).…”
Section: Altered Mentation Due To Cns Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, sedation is a relatively common CNS side-effect of epidurally administered alpha-2 agonists, opioids and dissociative drugs (Table 1). In contrast, CNS excitation is a rare side-effect and has only infrequently been reported in horses after the epidural administration of large doses tiletamine/zolazepam (Natalini et al 2004a) and the opioids morphine and tramadol (Giorgi et al 2010;Mirra et al 2020).…”
Section: Altered Mentation Due To Cns Effectsmentioning
confidence: 99%
“…The epidural route of administration minimises the risk of such systemic side-effects. However, epidural opioids have still occasionally been reported to cause mild GI symptoms, such as temporarily decreased GI motility, decreased frequency of defaecation or mild reduction of faeces, but without the concurrent occurrence of colic (Freitas et al 2011;Sano et al 2011;Kjaerulff et al 2021;Mirra et al 2020). In addition, one study also reported that horses may experience defaecation difficulties after the caudal epidural administration of lidocaine (Olbrich and Mosing 2003), which probably occurs primarily as a result of the indiscriminate blockade of sensory and motor nerves innervating the anus and rectum.…”
Section: Gastrointestinal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The placement of epidural catheters for continuous caudal epidural therapy in horses was first reported in 1983 and has become more frequently implemented clinically to employ multi-modal analgesic therapies ( 3 , 14 , 17 – 24 ). Caudal epidural catheters have been placed for continuous anesthesia and analgesia for surgical procedures as well as for pain management for orthopedic, rectal, and urogenital conditions ( 3 , 14 , 18 , 19 , 21 , 25 ). Continuous or repeated epidural administration of analgesics offers the advantages of effective analgesia with reportedly fewer side effects than systemic analgesics ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous or repeated epidural administration of analgesics offers the advantages of effective analgesia with reportedly fewer side effects than systemic analgesics ( 26 , 27 ). Despite its more frequent application in experimental and clinical settings, there are limited reports on the use of caudal epidural catheterization for long-term administration of epidural analgesics ( 18 , 21 , 24 , 25 ). In an experimental, prospective study on ten horses, no catheter-related complications, such as dislocation, catheter obstruction, leakage, or discomfort during injection were observed during a 14-day experimental observation period ( 24 ).…”
Section: Introductionmentioning
confidence: 99%